ANALISIS PSIKOLOGIS POLA KOMUNIKASI MAHASISWA MELALUI SMS KEPADA DOSEN - Aryanti, Zusy (JURNAL TAPIS, 2015)
This research is aimed at describing the communication pattern between the lecturers and their students at State Islamic College of Jurai Siwo Metro via Short Message Service media. The pattern can be seen from psychological analysis. The modern era brings us to use some technologies that help us to do our tasks in more convenient way. In contrast the ease in communication does not always make the communication effective. Sometime the meaning of the sentences written by the students is not clear enough and lead to the negative effects from the lecturers, such as feeling bad mood, feeling peeved, and neglecting the message.Keywords: Psychological analysis,Â  pattern, student, and lecturer